AKSJOLOGIA LIBERALNEJ I KOMUNITARYSTYCZNEJ WIZJI SPOŁECZEŃSTWA OBYWATELSKIEGO Z PERSPEKTYWY ALFREDA SCHÜTZA KONCEPCJI MOTYWÓW DZIAŁANIA - Szymczak, Wioletta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is to analyze the axiological foundations and purposes of social engagement in two directions in the reflection on civil society: the republican and liberal. The article seeks to answer the questions: what ideas of motives of contextual and goal-oriented citizen actions emerge from these two concepts of civil society? What values would create the constitutive elements of potential motives relating to the past as well as the objectives of the action in these discussed trends? What values would point to the goal of citizen engagement in a certain type of society? The analysis has been performed from the perspective and application of the concepts of sociology of understanding, and in particular Alfred Schütz’s concept of motivation to act. This discussion is supplemented with the specifics of civil societies in post-communist countries.